2002
DOI: 10.1021/jo0204303
|View full text |Cite
|
Sign up to set email alerts
|

Acidity of Adenine and Adenine Derivatives and Biological Implications. A Computational and Experimental Gas-Phase Study

Abstract: The gas-phase acidities of adenine, 9-ethyladenine, and 3-methyladenine have been investigated for the first time, using computational and experimental methods to provide an understanding of the intrinsic reactivity of adenine. Adenine is found to have two acidic sites, with the N9 site being 19 kcal mol(-1) more acidic than the N10 site; the bracketed acidities are 333 +/- 2 and 352 +/- 4 kcal mol(-1), respectively. Because measurement of the less acidic site can be problematic, we benchmarked the adenine N10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
138
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(152 citation statements)
references
References 62 publications
13
138
1
Order By: Relevance
“…22 Thus, as indicated by previous studies, gas-phase acidities can be informative regarding the leaving ability of a nucleobase within a hydrophobic active site, and may be relevant to the mechanism of substrate discrimination. 44,71 We therefore examined the dependence of hTDG activity on N1 acidity in a non-polar environment by calculating the gas phase N1 acidities of the nucleobases at 298 K (ΔG acid,g , Table S1, Supporting Information). (For comparison with other studies, the more commonly reported deprotonation enthalpies at 0 and 298 K are also given).…”
Section: Linear Free Energy Relationships For N-glycosidic Bond Hydromentioning
confidence: 99%
“…22 Thus, as indicated by previous studies, gas-phase acidities can be informative regarding the leaving ability of a nucleobase within a hydrophobic active site, and may be relevant to the mechanism of substrate discrimination. 44,71 We therefore examined the dependence of hTDG activity on N1 acidity in a non-polar environment by calculating the gas phase N1 acidities of the nucleobases at 298 K (ΔG acid,g , Table S1, Supporting Information). (For comparison with other studies, the more commonly reported deprotonation enthalpies at 0 and 298 K are also given).…”
Section: Linear Free Energy Relationships For N-glycosidic Bond Hydromentioning
confidence: 99%
“…Chen et al 8 measured a GPA of 14.1 eV (325.2 kcal/mol) for the most acidic site of gaseous adenine by using negative chemical ionization mass spectrometry. Lee et al 9 recently measured the gas-phase acidities of N9 and the NH 2 group by bracketing the gas-phase acidities (also in terms of deprotonation ∆H) of adenine, 9-ethyladenine, and 3-methyladenine by using a dualcell Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR). They concluded that 9H-adenine has two acidic sites: N9 and NH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In this research, we conducted quantum mechanical computations aiming at quantifying the effects of structural variations in adenine on the hydrogen bonding interaction (pairing) with thymine. As already discussed in the introductory section, derivatives of the nucleobases have been shown to possess biological activities and potential for clinical applications [16][17][18][19][20][21][22][23][24][25][26][27][28]. It was also of interest to analyze the impact of structural changes on the geometries of the formed complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental and theoretical investigations on hydrogen bonding involving structural fragments of biopolymers are the subject of continuing interest [12][13][14][15]. Literature data reveal that structurally modified DNA bases may possess substantial biological activity [16][17][18][19][20][21][22][23][24][25][26][27][28]. For example, halogenated pyrimidines have been shown to possess well-expressed anti-tumor, anti-bacterial and anti-viral effects [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation